Avaliação da eficiência de três métodos utilizados como controle da qualidade dos exames citopatológi- cos cervicais classificados como negativos no escrutí- nio de rotina - MANRIQUE, Edna Joana Cláudio (2008)
This study compared the effectiveness of quick review 100%, 10% random review and revision of smears selected based on clinical criteria as a method of internal quality control of cervical smears negative on routine screening and found that the false-negative results identified by review rapid vary with the quality of the sample and the woman's age. Was based on the female population user of the Unified Health System in Goiânia-GO, which was subjected to cytological examination performed at the Laboratory of Clinical Analysis of the Romulus Rock School of Pharmacy, Federal University of Goiás The 5,530 smears classified as negative scrutiny underwent routine method for quick review 100%, then the smears were selected based on clinical criteria and 10% of negative smears and submitted to the respective revisães. Four cytologists alternated during revisions. After the revisions concordant results were considered final diagnosis, whereas the divergent were analyzed by a third cytologist, which consensus meeting defined the final diagnosis. All steps were blindly and the results classified according to the Bethesda System. For statistical analysis, the variables were analyzed descriptively and applied the chi-square test. A Quick Review of 100% smears identified 141 suspects, 84 of these (59.6%) tested positive for the final diagnosis, of which 36 (25.5%) were classified as atypical squamous cells of undetermined significance (ASC-US) five (3.5%) as atypical squamous cells can not exclude high-grade lesion (ASC-H), 34 (24.1%) as squamous intraepithelial lesions of low-grade (LSIL), six (4.3 %) as squamous intraepithelial lesion, high-grade (HSIL) and three (2.1%) atypical glandular cells (AGC). Smears of 84 suspected and confirmed the final diagnosis, 62 (73.8%) were classified as satisfactory and 22 (26.2%) satisfactory, but with some limitation, but no significant difference was with the woman's age. The method of rapid review identified 19 as unsatisfactory smears, 16 of these (84.2%) were confirmed in the final diagnosis. Of the 1,279 smears reviewed based on clinical criteria, 24 were considered abnormal. Of these 19 (79.2%) were confirmed as positive by the final diagnosis, nine (47.3%) classified as ASC-US, one (5.3%) ASC-H, eight (42.1%) and LSIL One (5.3%) HSIL. Of the 560 smears examined by reviewing 10%, 13 were considered abnormal, these six (46.2%) were confirmed in the final diagnosis, four (30.8%) classified as ASC-US, one (7.7%) and LSIL (7.7%) HSIL. Therefore, a quick review of 100% is a more efficient alternative for the detection of false-negative results of cervical screening as a method of internal quality control, than the random review of 10% and revision based on clinical criteria. It was observed also that the quick review showed better performance when the sample was classified as adequate for analysis, but does not vary with the age of the woman.